(3GdJfHjg Ydi eG hLH ef ENQGL GdjghO ef LRjQI GdYQHs - (3UGQe GdOjf EHQGgje Hf YHO GdbGOQ Hf CMeO GdchcHGfj, GdchcHGfj,J (B1223 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bdJe OGeJ EaGOJce (B: (3hbY GdHMK ai QSGdJi GdbGVi CMeO Hf UGdM , hGdbGVi MSjf GdeZQHi ai JMQjQ COdI ENQGL GdjghO ef LRjQI Gdjef s
(3BNQgG (B:s
(3hGddg jbhd GdMb hgh jgOi GdSHjd GfJgi s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B48s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B126 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs